Analysis the Impact of Literature on the Formation of the Russian Federation State Civil Servant Image in Mass Media - Evstratova, Tatiana A. (2020)
The main features of the XXI century Russian society have been formed due to social and psychological changes, which led to a global transformation of the state system. Modern world faces the problem of developing a new policy of state power that will be based on the principles of consensus (reconciliation of all contentious and conflicting issues in the process of developing a solution that is reached through discussion and consultation), society and open partnership. The reason for this global upheaval is that the pace of change in the relationship between the state (government) and society itself depends on the open-ended policy that is now key. The image of a civil servant is similar to a construction that can be replaced, strengthened, re-mounted, modified, etc., and most importantly, that it needs serious work. The perception of the image exists and changes not only in the consciousness of people, but also in the unconscious sphere (emotional). In order to create a positive image of a civil servant, they need to be governed. To manage it, one needs to know the basic idea of what and in what sequence should occur, and at what stage intermediate results should appear. According to the authors, the solution to the problem of studying the acting factors that make the positive image of civil servants of modern Russia, the identification of the most effective ways, forms and principles of its positive transformation, as well as the analysis of the constituents of the employee of state structures are relevant. The most important in the work of representatives of public authorities is the nature of their public relations. If public servants do not evoke citizens' feelings of trust, justice and other positive psychological and social reactions, then feedback (from the population to state bodies) will be ineffective. Since the operation of the system of state power is the result of the functioning of the whole state as a whole, it is important that the work of state bodies used the maximum opportunities with the least cost. This scheme ensures effective management and positive results. But such a situation will not be achievable if the level of public trust in government is low.